2018
DOI: 10.1038/s41467-018-06283-1
|View full text |Cite
|
Sign up to set email alerts
|

CD69 prevents PLZFhi innate precursors from prematurely exiting the thymus and aborting NKT2 cell differentiation

Abstract: While CD69 may regulate thymocyte egress by inhibiting S1P1 expression, CD69 expression is not thought to be required for normal thymocyte development. Here we show that CD69 is in fact specifically required for the differentiation of mature NKT2 cells, which do not themselves express CD69. Mechanistically, CD69 expression is required on CD24+ PLZFhi innate precursors for their retention in the thymus and completion of their differentiation into mature NKT2 cells. By contrast, CD69-deficient CD24+ PLZFhi innat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…This result confirms our original study, where we reported the NKT cell proportion among NKT cells to vary between 0.2% and 0.5% in 2‐ to 5‐week‐old C57BL/6 mice 34 . However, numerous studies investigating NKT cell development report a higher proportion, varying from 3% to 17% . The unusually high proportion of HSA high NKT cells reported in these studies may be a result of the absence of enrichment strategies or inefficient application of such strategies, resulting in contamination of the HSA high NKT cell with conventional T cells or cortical thymocytes.…”
Section: Nkt Cell Identification During Positive Selectionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result confirms our original study, where we reported the NKT cell proportion among NKT cells to vary between 0.2% and 0.5% in 2‐ to 5‐week‐old C57BL/6 mice 34 . However, numerous studies investigating NKT cell development report a higher proportion, varying from 3% to 17% . The unusually high proportion of HSA high NKT cells reported in these studies may be a result of the absence of enrichment strategies or inefficient application of such strategies, resulting in contamination of the HSA high NKT cell with conventional T cells or cortical thymocytes.…”
Section: Nkt Cell Identification During Positive Selectionsupporting
confidence: 89%
“…Although these cells did not bind unloaded CD1d tetramers, they have not been checked for Vβ8 or CD69 expression. A more recent study analyzed the phenotype of HSA high NKT cells obtained without using an enrichment strategy, and found that stage 0 NKT cells consisted of CD44 low and CD44 high subpopulations, named stage 0a and stage 0b, respectively 38 . Both subsets express CD4 and CD8 and are thus HSA high DP thymocytes.…”
Section: Nkt Cell Identification During Positive Selectionmentioning
confidence: 99%
“…Conversely, iNKT0 expressed CD69, while iNKT2b and iNKT1a/b subsets expressed Cxcr3 (Figure 4A), two genes encoding for proteins involved in thymic retention (Drennan et al, 2009;Weinreich and Hogquist, 2008). To test these observations in vivo, we attempted to block iNKT thymocyte egress by means of FTY720 (Kimura et al, 2018), a selective sphingosine 1-phosphate receptor agonist that induces its internalization (Mandala et al, 2002). Prolonged FTY720 treatment led to a significant increase in iNKT thymocytes (Figure 4B).…”
Section: Multiple Inkt Subsets Have the Potential To Egress The Thymusmentioning
confidence: 99%
“…TCR stimulation increases H3K4 methylation at the Cd69 gene in naïve CD4 T cells, suggesting that the expression of CD69 is epigenetically regulated (94). More recently, CD69 has been found to be crucial for maturation of NKT2 cells in the thymus, where CD69 prevents immature precursors from exiting by suppressing the sphingosine-1-phosphate receptor 1 (S1P 1 ) expression (95). A number of studies have reported roles of CD69 in murine models of inflammatory diseases, including arthritis, airway inflammation, and dextran sulfate sodium (DSS)-induced colitis (9698).…”
Section: The Regulation Of the Recall-responses Of Effector And Memormentioning
confidence: 99%